Dengue encephalitis presenting as febrile status epilepticus: A case report - V S V Prasad (Wolters Kluwer Medknow Publications, 2015)
Dengue fever is the most important Arboviral infection in the world, with an estimated 100 million cases of dengue infection worldwide eveiy year with a large proportion of patients being children (1). Encephalitis is a rare complication of dengue virus infection and may occur as a consequence of intracranial hemorrhage, cerebral edema, hyponatremia, cerebral anoxia, release of toxic products or direct viral invasion.